Cultural contact and barrier effects in the diffusion of innovations by examples from East Africa - Nordström, Olof (Fennia - International Journal of Geography, 1981)
<!--[if gte mso 9]> <![endif]--> <span style="font-size: 8.5pt; line-height: 115%; font-family: "Arial","sans-serif"; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-GB; mso-fareast-language: FI; mso-bidi-language: AR-SA;" lang="EN-GB">The environment, into which an innovation, spontaneous or controlled, is to be introduced, has not been sufficiently examined in Swedish geographical innovation research, which must be considered a serious shortcoming. The same applies to many modern development assistance operations in the developing countries, which has had a consequence that the goals have not been reached. It is shown how a comparatively advanced culture as the Swahili culture in a number of urban enclaves along the East African coast has or has not affected the Interior of Africa. The most important task has been to map and analyse the barriers that have existed between the Swahili peoples and the farming and cattle‑raising peoples in East Africa and have prevented the transfer of different forms of know‑how <!--[if gte mso 9]> Normal 0 21 false false false FI X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->